The Effect of Functional Play towards Gross Motor Skill for Children with Autism - Susi Marta Handayani; Sudarsini Sudarsini; Endro Wahyuno (Journal of ICSAR, 2018)
The development of gross motor skill for children with autism mostly is not appropriate with their chronological age. Particularly, it is occurred to the coordination ability such as throwing and catching ball, which emphasized on the strength, endurance, and movement direction. This research was conducted by using Single Subject Research method with A-B-A design and using frequency and percentage as measurement unit. The research subject was a child with mild autism. The research result showed that: mean level of mean improved from baseline-1 of 31.32%, intervention of 61.7%, and baseline-2 of 82.15%. Data of overlap percentage between baseline-1 and intervention condition was 0%. Functional play could improve gross motor skill in throwing and catching ball in the strength, endurance, and movement direction. Therefore, functional play – sitting and lying on the gym ball – could be made as recommendation in improving or optimizing gross motor skill such as throwing and catching ball to the children with autism.